Development of Tourism Village on The Basis of Tourist Typology (The Case of Pematang Johar Tourism Village, Deli Serdang Regency - Emrizal; Ria Tamba; Sitti Nurlaeli (Tourism, Hospitality And Culture Insights Journal, 2021)
The purpose of this study is to determine the typology of tourists visiting Pematang Johar Tourism Village and to analyze the implications of the findings for planning the development of tourism villages in the future. Survey method was used to collect data. 110 respondents were involved in this study. The data analysis was done by using Plog's psychographic typology model. The results showed that the majority of visitors to Wisata Sawah Pematang Johar belonged to the pro-allocentric group, followed by the mid-centric type and the pro-psychocentric group. The implications of the findings are discussed for the purposes of planning and developing tourism products and services in the tourist village of Wisata Sawah Pematang Johar.